Recalibrating Parate Executie, Navigating Legal Pluralism, Criminalization Risks and Procedural Governance In Indonesian Fiduciary - Lumban Gaol, Chandra Erick Manaek Pandapotan; Abubakar, Lastuti; Marpaung, Roni Heilig (Universitas Internasional Batam, 2025)
The landscape of fiduciary execution (jaminan fidusia) in Indonesia has been fundamentally reshaped by Constitutional Court Decisions No. 18/PUU-XVII/2019 and No. 2/PUU-XIX/2021. These landmark rulings, while aiming to bolster debtor protection under the 1945 Constitution, have curtailed the creditor's right of direct execution (parate executie) as originally established by Law No. 42 of 1999. This judicial intervention has engendered a state of profound legal ambiguity, creating a perilous enforcement vacuum where the lines between lawful execution and criminal conduct have become dangerously blurred. This article employs a normative legal research methodology, incorporating doctrinal, statutory, case, and comparative approaches to analyze this complex legal problematic. We argue that the Court's decisions, by introducing the vague and procedurally undefined prerequisites of a post-default